Circular economy implementation and business performance: The mediating role of environmental performance in the Chinese energy production enterprises - Dong, Hao; Wang, Bo; Li, Jiaze; Li, Zongwu; Li, Fujing; Wang, Chuangjia (Frontiers in Environmental Science, 2022)
This study proposes a model to explain the effect of circular economy implementation on business performance in the Chinese energy production enterprises. Moreover, it analyzes the mediating role of environmental performance in explaining the influence mechanism. Our study used data from the Chinese energy production enterprises, which included 295 firms. We applied the methodological approach, partial least square structural equation modeling (PLS-SEM), to test the hypothetical model. The results show that circular economy implementation have a positive on business performance, and environmental performance plays a part of the intermediary role in the circular economy implementation affecting business performance. Finally, some promising avenues for future research and implications for managers and policymakers are suggested based on these findings.